A Simple, Mild, and Practical Method for the Esterification and Thioesterification of Anthranilic Acid Utilizing N-(2-Aminobenzoyl)benzotriazole - Kökten, Şule; Çelik, İlhami (Synthesis, 2013)
A convenient and efficient method for the preparation of anthranilic esters and anthranilic thioesters has been developed by the treatment of N-(2-aminobenzoyl)benzotriazoles with alcohols and thiols in the presence of 4-(dimethylamino)pyridine (DMAP).
Keywords: alcohols; esterification; esters; heterocycles; thiols